Modern Electronic Resources as a Factor of Integration in the System of Medicine Scientific Communication - Tymoshenko Inessa (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2020)

(untitled)
The article analyzes the modern electronic resources, their practical orientation and evaluation of significance of new communication tools in the healthcare system of scientific communication. The author raises the issue of the difficulty of mastering new communication tools, which need to be overcome by appropriate solutions aimed at creating a unified medical information space, including electronic. The analysis uses the proposed system of basic types of information and communication tools of biomedical electronic resources: electronic publications, electronic libraries.And as the development of technology for access to scientific literature has emerged, several areas, combined by the common slogan − open access. The Open Access Initiative proclaims the basic principles of using new opportunities for electronic publications to ensure broad access and exchange of views of scientists, with the importance of maintaining peer review, archiving scientific publications, and respecting copyright.Development of the system of scientific and especially medical information could be considered as the part of state policy. Conferences help to exchange experience, as well as scientific information services in medical libraries.In Ukraine, creation of an integral medical information electronic space is in demand. There is an urgent need to develop a system for exchange electronic resources, including researches, between universities. There is a need to develop a system for the exchange of scientific electronic resources between scientific institutions, universities, the National Scientific Medical Library of Ukraine.Proposed new scientific directions are offered, aimed at changes of components, subsystems and replenishment with new elements, which significantly influences modern models of scientific communication and creation of fundamentally new communication resources of domestic information systems